Kajian Desain Healing Garden di RSUD Ahmad Yani sebagai Media Terapi Psikologis Berdasarkan Persepsi dan Preferensi Tenaga Kesehatan - Indah Nurrohimah; Indung Sitti Fatimah; Prita Indah Pratiwi (http://arl.faperta.ipb.ac.id/, 2023)
In urban communities, the Covid-19 pandemic has caused psychological and mental disorders. Health workers are most affected and vulnerable to psychological disorders, especially those working at Covid-19 referral hospitals such as the Ahmad Yani Hospital. As a result, psychological therapy facilities or media that can improve the psychological health of health workers are needed. The research aimed to determine the urgency and need for healing gardens among health workers, to know about health workers' perceptions and preferences regarding healing garden design, and make recommendations on criteria and design concepts for healing gardens in the Ahmad Yani Hospital area. The study's methods included the distribution of questionnaires and interviews. Descriptive analysis with crosstabulation and frequency techniques is used. A healing garden in the Ahmad Yani Hospital area is regarded as necessary as a psychological therapy medium for improving the psychological health of health workers. During the Covid-19 pandemic in the hospital environment, 97.3% of participants said they needed a green open space that functions as a relaxation area to improve psychological health, and 94.6% said they needed a healing garden. Colour parameters, materials, concepts, space, plants, plant strata, plant functions, facilities, areas/locations, and healing garden criteria are all preferences for health workers. Health workers' preferences for healing garden design are generally relatively consistent across gender and age groups. A nature-oriented healing garden design is the recommended healing garden design for the Ahmad Yani Hospital area (biophilic design).